An efficient in vitro total reconstitution of the Escherichia coli 50S ribosomal subunit - Amils, Ricardo (1978)
A new, relatively simple technique for the total invitro reconstitution of E. coli 50S ribosomes has been developed. It is a two-step procedure like that previously reported by Nierhaus and Dohme [Proc. Natl. Acad. Sci. 71, 4713 (1974)], but it differs in a number of important aspects. Ribosomal RNA is prepared by direct phenol extraction of 70S particles to minimize nuclease fragmentation. A mixture of 50S proteins is prepared by acetic acid extraction and immediate removal of the acetic acid by thin film dialysis. The resulting protein mixture is soluble and stable. Separate RNA and protein fractions are mixed, incubated first at 44°C in 7.5 mM Mg(2+), and then at 50°C in 20 mM Mg(2+). The resulting 50S particles comigrate with native 50S particles in analytical gradients. They range from 50 to 100% active in five different functional assays. This is a fairly stringent test of the effectiveness of reconstitution since 50S particles derived from highly active vacant couples were used as a control.